Edukasi Pertambangan Berwawasan Lingkungan pada Mahasiswa Teknik Geologi Universitas Sulawesi Tenggara - Saleh, Isman; Arisona Arisona; Okto, Ali; Arifin, Asri; Bahdad Bahdad; Masri Masri; Jaya, Rio Irhan Mais Cendra; Firdaus, Amritzal Nur (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to enhance the understanding of Geology Engineering students at Universitas Sulawesi Tenggara regarding environmentally sustainable mining practices. The education was delivered through lectures, interactive discussions, and local case studies relevant to mining activities in Southeast Sulawesi. These methods were chosen to encourage active participation and ensure the materials were contextually relevant to the students’ local environment and future professional field. The results indicate that students gained new insights into the implementation of good mining practice, post-mining reclamation, and mining and environmental regulations, which fostered greater awareness of the environmental and social impacts of mining. In addition, the program facilitated critical thinking and encouraged students to analyze real-world mining problems from a sustainability perspective. Consequently, this program not only improved students’ environmental literacy but also developed a sense of responsibility and commitment to supporting sustainable mining practices. It is expected that the knowledge gained will influence their future decisions as professionals in the mining sector, promoting a more sustainable and responsible industry.